1999
DOI: 10.1081/pdt-100101361
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Polyethylene-Glycol-Modified Salmon Calcitonins

Abstract: The conjugation of salmon calcitonin (sCT) by covalent linkage of polyethylene glycol (PEG) was attempted to overcome several disadvantages of sCT as a therapeutic drug, namely its rapid clearance from blood circulation and enzymatic degradation. The polymer employed was succinimidyl carbonate monomethoxypolyethylene glycol (12 kDa). Superose HR size-exclusion chromatography was applied to separate the PEGylated sCTs (mono-PEG-sCT and di-PEG-sCT) from the unmodified sCT. The PEGylation of sCT was verified by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…To reduce metabolism, a linear lys-18-PEG 2K -sCT displayed enzymatic stability, reduced systemic clearance and enhanced hypocalcaemia following intra-duodenal administration to rats [34]. Another sCT-mPEG conjugate with mono-and di-mixtures also had reduced clearance and an extended T 1/2 compared to unmodified sCT [35]. For the sCT-Lys 18 -PEG conjugates, increased proteolytic stability and an extended T 1/2 are clearly associated with increased PEG MW [36].…”
Section: Discussionmentioning
confidence: 99%
“…To reduce metabolism, a linear lys-18-PEG 2K -sCT displayed enzymatic stability, reduced systemic clearance and enhanced hypocalcaemia following intra-duodenal administration to rats [34]. Another sCT-mPEG conjugate with mono-and di-mixtures also had reduced clearance and an extended T 1/2 compared to unmodified sCT [35]. For the sCT-Lys 18 -PEG conjugates, increased proteolytic stability and an extended T 1/2 are clearly associated with increased PEG MW [36].…”
Section: Discussionmentioning
confidence: 99%
“…It has demonstrated reduced immunogenicity, extended circulating half-life, and improved stability for these therapeutic agents. 1,2 PEGylated molecules are among the most challenging products to characterize because of the heterogeneity with respect to distribution in both the number and position of the attached PEG molecules, and the inherent polydispersity of PEG itself. 3 When developing PEGylated biomolecules as therapeutic agents, various points should be considered including characterization of starting materials (protein and PEG molecule), determination of PEGylation sites, and stoichiometry of PEG attachment.…”
mentioning
confidence: 99%
“…[15][16][17] Furthermore, it has been reported that hydrogel having PEG chain on its surface shows the mucoadhesive ability by interaction with mucosa. 18) In this study, we investigated the effect of PEGylating polycations on their permeation enhancement to develop superior absorption enhancers.…”
mentioning
confidence: 99%